ACTUAL PROBLEMS OF THE HISTORY, LANGUAGE, AND LITERATURE OF TURKIC PEOPLES - Umarov Bobir Norboyevich (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article examines the actual problems in the study of the history, language, and literature of Turkic peoples within the context of globalization and socio-political transformation. The research analyzes methodological challenges in historiography, including the legacy of imperial and Soviet interpretations, and emphasizes the need for comparative Eurasian and interdisciplinary approaches. The study also explores contemporary linguistic issues such as alphabet reforms, terminology development, and the impact of globalization on language preservation. In addition, the article highlights the reinterpretation of classical literary heritage and the challenges faced by modern Turkic literature in balancing national identity with global integration. The findings suggest that coordinated academic cooperation, methodological innovation, and cultural policy harmonization are essential for strengthening Turkic studies as a dynamic and influential field of scholarship.